Russian Federation : Targeted Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2011)
This paper focuses on targeted detailed assessment of observance of the Basel Core Principles for effective banking supervision. The selection of the principles to be reassessed was made by the mission team based on an analysis of the risks and vulnerabilities of the Russian Federation. It was revealed that the Central Bank of Russia (CBR) Law does not establish requirements for banks to seek prior CBR approval when making domestic investments in nonbank financial institutions.